Changes in isometric mid-thigh pull peak force and symmetry across anterior cruciate ligament reconstruction rehabilitation phases - Stofberg, Johannes P. J.; Aginsky, Kerith; van Aswegen, Mariaan; Kramer, Mark (Frontiers in Rehabilitation Sciences, 2024)
BackgroundWhether functionally relevant strength assessments, such as the isometric mid-thigh pull (IMTP), can be used either bilaterally or unilaterally to evaluate and guide rehabilitation progress in those with anterior cruciate ligament reconstruction (ACLR) is under-researched. This study assessed changes in peak force (PF) and asymmetry across 3 phases for bilateral and unilateral IMTP assessments in patients with ACLR. Peak isometric force from the IMTP was compared to peak torque from isokinetic dynamometry as well as against a cohort of healthy, uninjured individuals.MethodParticipants (ACLR, n = 15) completed bilateral and unilateral IMTP assessments at weeks 12 (baseline), 16 (phase 3), and 20 (phase 4) of rehabilitation to evaluate changes in PF and asymmetry. Asymmetry was evaluated using the asymmetry angle. Isometric data from the IMTP were compared to that from an isokinetic dynamometer as well as against a cohort of healthy, uninjured participants (n = 63) allowing for a detailed analysis of limb-specific force production.ResultsThe PF during the bilateral IMTP increased for both the injured (0.94 N/kg) and uninjured (0.26 N/kg) limbs from baseline to phase 4, whereas the PF of the injured limb increased by 1.5 N/kg during the unilateral IMTP in the same time frame. Asymmetry values systematically reduced by ∼1% and ∼0.5% for the bilateral and unilateral IMTP tests from baseline to phase 4. Significant differences in PF of the injured limb were evident between those with ACLR and healthy controls across all phases (p = 0.022–0.001). The rate of progression in PF capacity was dependent on test type, amounting to 0.1 and 0.2 body weights per week for the bilateral and unilateral IMTP respectively. Small-to-large correlations (r = 0.12–0.88) were evident between IMTP PF and peak torque from the isokinetic dynamometer as well as between asymmetry metrics from both tests.ConclusionThe findings suggest that IMTP PF has potential for monitoring changes in PF and asymmetry during the ACLR rehabilitation progress. Both injured limb and uninjured limb show improvement in force-generating capacity, implying a positive adaptation to rehabilitation protocols. The findings highlight that ACLR is a unilateral injury that requires bilateral rehabilitation.